Phytochemistry and In vitro Antimicrobial Activity of Five Plant Species against Nine Common Human Pathogens (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Momordica charantia, Senna podocarpa, Senna alata, Ocimum gratissimum, and Sida acuta which have reportedly been used in folklore for the treatment of various diseases were studied for their antimicrobial activity. Crude methanolic extracts of the leaves were screened for phytochemicals after which they were tested in vitro for activity against clinical isolates of Staphylococcus aureus, Klebsiella oxytoca, Pseudomonas aeruginosa, Proteus vulgaris, Bacillus subtilis, Enterobacter aerogenes, Aspergillus niger, A, flavus and Candida albicans. Phytochemicals present in the extracts included saponins, alkaloids, anthraquinones, tannins, flavonoids and cardiac glycosides. These extracts also showed varying degrees of activity against tested organisms at a concentration range of 15.6 to 500 mg/ml. However, S. acuta showed activity against P. vulgaris, E. aerogenes and As. flavus only. The MIC of the extracts against test organisms ranged from 31.25 to 250 mg/ml. The significant antimicrobial susceptibility of the plant extracts against gram positive bacterial pathogens and some pathogenic yeasts, may not be due to the presence and synergistic interactions of secondary metabolites found in these plant extracts. This would have implications in health, particularly in developing countries where a singnificant percentage of the population are still using traditional plant extracts for health care.Dhaka Univ. J. Pharm. Sci. 20(2): 139-148, 2021 (December)